2020
DOI: 10.21203/rs.2.11817/v5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combined use of apatinib mesylate  and vinorelbine versus  vinorelbine alone in recurrent or metastatic  triple-negative breast cancer: study protocol for a randomized controlled clinical trial

Abstract: Background: The emergence of new molecular targeted drugs provides new prospects for the treatment of advanced breast cancer; the future therapeutic trend includes chemotherapy combined with molecular targeted therapy. Apatinib mesylate, a novel, small anti-angiogenic agent, highly selectively inhibits the activity of vascular endothelial growth factor receptor-2 tyrosine kinase. Apatinib mesylate also blocks the signaling of vascular endothelial growth factor binding to its receptor, thereby strongly inhibiti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Apatinib [14,15] is a potent inhibitor of vascular endothelial growth factor receptor 2 (VEGFR2), which exerts anticancer effects by inhibiting the binding of vascular endothelial growth factor (VEGF) to its receptor (VEGFR), thereby inhibiting tumor angiogenesis and ultimately leading to tumor cell proliferation inhibition due to the resultant tumor hypoxia. Studies have shown that TNBC patients exhibit signi cant VEGF expression, con rming that VEGFR is an effective therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…Apatinib [14,15] is a potent inhibitor of vascular endothelial growth factor receptor 2 (VEGFR2), which exerts anticancer effects by inhibiting the binding of vascular endothelial growth factor (VEGF) to its receptor (VEGFR), thereby inhibiting tumor angiogenesis and ultimately leading to tumor cell proliferation inhibition due to the resultant tumor hypoxia. Studies have shown that TNBC patients exhibit signi cant VEGF expression, con rming that VEGFR is an effective therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…Apatinib (APA) is an oral small-molecule antiangiogenic drug and can selectively inhibit the tyrosine kinase activity of intracellular VEGFR2 and suppress the interaction between VEGF and VEGFR, exerting an antiangiogenic effect. Clinically, APA is mainly used as the third line treatment of advanced gastric cancer and gastroesophageal junction adenocarcinoma, and the efficacy and adverse reactions of APA in the treatment of TNBC are still being investigated in clinical trials [11][12][13].…”
Section: Introductionmentioning
confidence: 99%